Lone Parents and Social Security - Hughes, John (Victoria University of Wellington Law Review, 2005)
The domestic purposes benefit for lone parents has been politically charged since its inception. This article examines the developing case law relating to the benefit, with particular reference to the interrelationship between the relevant social security principles and wider issues of family policy.